2022
DOI: 10.1029/2021gb007242
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Patterns of Aged Organic Carbon Export Driven by Hydrologic Flow Paths, Soil Texture, Fire, and Thaw in Discontinuous Permafrost Headwaters

Abstract: Climate change is thawing and potentially mobilizing vast quantities of organic carbon (OC) previously stored for millennia in permafrost soils of northern circumpolar landscapes. Climate‐driven increases in fire and thermokarst may play a key role in OC mobilization by thawing permafrost and promoting transport of OC. Yet, the extent of OC mobilization and mechanisms controlling terrestrial‐aquatic transfer are unclear. We demonstrate that hydrologic transport of soil dissolved OC (DOC) from the active layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
(161 reference statements)
0
5
0
Order By: Relevance
“…We observed a slow steady rise in solute concentrations in the lake prior to 2019 (Figures 6 and 9). Others have observed similar increases in solute concentrations, which are attributed to deeper hydrologic flow through thickening active layers (Keller et al, 2010; Koch et al, 2022; Kokelj et al, 2009). This slow rise was followed by an abrupt increase in solutes in 2019, coincident with the appearance of groundwater seeps at the base of the footslope (Figure 4B).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…We observed a slow steady rise in solute concentrations in the lake prior to 2019 (Figures 6 and 9). Others have observed similar increases in solute concentrations, which are attributed to deeper hydrologic flow through thickening active layers (Keller et al, 2010; Koch et al, 2022; Kokelj et al, 2009). This slow rise was followed by an abrupt increase in solutes in 2019, coincident with the appearance of groundwater seeps at the base of the footslope (Figure 4B).…”
Section: Discussionmentioning
confidence: 74%
“…The return to prefire concentrations we observed may be due to complex interactions taking place in the warming soils and solutes entering the lake. Koch et al (2022) recently demonstrated DOC concentrations increase with seasonal active layer thickening, and that DOC age was older in catchments with >50% burn, indicating that carbon trapped in thawing permafrost was contributing DOC to the aquatic environment. Permafrost‐derived DOC is likely entering our study lake, as evidenced by our observations on water clarity, radiocarbon, and SUVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This division paradigm was based on municipal regions and allowed us a larger amount of data, thus reducing the impact of spatial heterogeneity and enhancing the accuracy and reliability of the results. Based on the new division mode, we imported the generalized additive model (GAM) to fit the complicated non‐linear relationships between selected indicators and the PT (Kim et al., 2019; Koch et al., 2022; Peng et al., 2023). Then we further explored the effects of various factors on drought propagation and the interaction between these factors from a spatial perspective by applying the geographic detector (GD) method (Luo et al., 2016; J. F. Wang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…in western Canada (Gibson et al, 2018), Siberia (Talucci et al, 2022), and Alaska (Mekonnen et al, 2022). Increases in the number and extent of fire events result not only in the immediate carbon loss through biomass burning but also an increase of downstream export of particulate and dissolved organic carbon (DOC) from the burned areas as summarized in Table 1 (Burd et al, 2018;Burd et al, 2020;Ackley et al, 2021;Koch et al, 2022;Mekonnen et al, 2022).…”
mentioning
confidence: 99%